2019
DOI: 10.5812/semj.86506
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Determinants of Healthcare Expenditures in Different Healthcare Systems

Abstract: Background:The rapid growth of health expenditures is a great concern for governments at present. Objectives: The present study aimed to determine the main factors affecting health care expenditures in countries with different types of the healthcare system. Methods: We studied 25 countries with different types of healthcare systems, including national health insurance, traditional sickness insurance, national health services, and mixed systems. Health expenditure per capita was estimated as a function of heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…have increased demand for medical care, thereby raising healthcare expenditure across economies, including the sub-Saharan Africa. 39,40,44,46,60,[62][63][64][65][66][67] This notwithstanding, marked decline in health expenditure in Japan as COVID-19 virus spread with strained medical resources has been reported. 64 The decrease in healthcare expenditure was due largely to considerable changes in people's behaviour regarding willingness to visit medical institutions for treating COVID-19 or any other illness.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…have increased demand for medical care, thereby raising healthcare expenditure across economies, including the sub-Saharan Africa. 39,40,44,46,60,[62][63][64][65][66][67] This notwithstanding, marked decline in health expenditure in Japan as COVID-19 virus spread with strained medical resources has been reported. 64 The decrease in healthcare expenditure was due largely to considerable changes in people's behaviour regarding willingness to visit medical institutions for treating COVID-19 or any other illness.…”
Section: Literature Reviewmentioning
confidence: 99%
“…65,66 Furthermore, studies found that rising income across countries and regions has engendered significant surge in healthcare expenditure. 8,14,39,40,45,46,55,63,67 When income increases, demand for health tends to escalate as a result of rising marginal utility from healthcare. 55,68 The level of income, which is categorised under socioeconomic factor can influence individual's "ability to transform the need for health services into affordable health services, which in turn affects the health expenditure growth."…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations